Chemical Safety and Quality Attributes of Dried Sausage Snacks Stored in Modified Atmosphere - Jagoda Majcherczyk; Ireneusz Maciejaszek; Krzysztof Surówka (International Journal of Food Science)
A sausage snack was produced by air blast drying of cottage sausage, and its safety and quality were investigated during 10-week storage period in a modified atmosphere (20% CO2/80% N2) at 4±1°C and 20±1°C. The results of a sensory and instrumental evaluation of colour and texture showed that significantly greater changes in these parameters were caused by drying the sausage rather than during subsequent storage of the produced snacks. Although total viable count increased and reached a maximum value of 6.5 log CFU g−1 after 70 days of storage at 20±1°C, Enterobacteriaceae were not detected. The histamine level was approx. 18 mg kg-1, while the average content of the other biogenic amines after 70 days of storage ranged from 4.4 mg kg-1 (cadaverine) to 32.1 mg kg-1 (tyramine). The biogenic amine index was small and varied from 34.5 mg kg-1 (in the sausage before drying) to 73.4 mg kg-1 (at the end of the snack storage at 20±1°C). The lipid hydrolysis and oxidation proceeded slowly and did not pose a threat to the product quality. The combination of drying and modified atmosphere packaging maintains good quality and safety of sausage snack during 70 days at refrigerated storage and/or 4 weeks at room temperature.